QUARTET LEARNING MEDIA AND STUDENT ARGUMENTATION: DEVELOPMENT ANALYSIS AND CORRELATION IN SCIENCE LEARNING IN JUNIOR HIGH SCHOOLS - Qolbyatin, Nur Asa; Septaria, Kiki; Wulandari, Siska Ayu (INSECTA: Integrative Science Education and Teaching Activity Journal, 2023)
Argumentation is essential in scientific learning activities because it helps students grasp concepts and apply their knowledge in real-life situations by presenting the same notion in multiple settings. The purpose of this study is to investigate students' scientific argumentation skills using a science quartet educational game. The Research and Development approach is used in this study, along with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model phases. This study's sample consisted of class VIIIB students from SMPN 2 Sugio, with a small group trial of 15 students and a large group test of 32 students, for a total of 47 individuals. Techniques for gathering data include observation, testing, and surveys. This study included four specialists: media experts, practitioners, material experts, and linguists. The validity test, N-gain, t-test, and correlation were used to examine the data. The validity test findings demonstrated the practicality of the scientific quartet educational game with percentages of 86% and 100%, indicating extremely valid categories. The science educational game quartet had an influence on students' scientific arguments with a significant value of 0.05, as indicated by an increase in the cognitive N-gain test results and students' scientific arguments by 0.75 (high category) after evaluating the paired sample t-test. The correlation test findings revealed a link between the science quartet educational game and students' science arguments with a significance value of 0.05, placing it in the strong positive category. The findings of the study show that science quartet educational game are useful in the learning process.